Implementation of Gamification in The Hotel Membership System for Repurchase - Anwar, Toni; Wijaya, Anugerah Bagus; Paramita, Cayadewi; Fathoni, Muhamad Zidan (Politeknik Negeri Ujung Pandang, 2021)
Javaheritage Hotel is a 4-star hotel located in the tourist city of Purwokerto. Java Heritage already has a membership system to increase consumers’ purchases back to the hotel. The current membership system allows consumers to purchase members who will get an active stay voucher for one year. Javaheritage requires increasing the number of repurchases by member and non-member consumers to Javaheritage hotels. Gamification applies scoring points, competition, and game rules to other activities or activities. This study aims to design a hotel membership system that implements gamification to increase repurchase at java heritage hotels. The output of this research is a research journal, and the TKT that will be achieved is at level 7. Namely, the Demonstration of a prototype system in a natural environment. The development method used is RAD (Rapid Application Development) and system design depiction using UML.